Soil moisture change and land use in Victoria, Australia. Issue 3 (2nd July 2016) - Buxton, M.; Osman-Schlegel, N. Y.; Lopes, D.
ABSTRACT: Soil moisture is a critical component of a wide range of human activities. Its decline correlates well with climate change. This study extends the examination of soil moisture in Victoria, Australia by the pioneering work undertaken in 1965 by G.D. Aitchinson and B.G. Richards. It examines trends in soil moisture in three, twenty-year, and six, ten-year periods from 1948–2007. This 60-year period includes a number of wet and dry periods and provides long-term trends that should be considered in assessing the impacts of climate change on land use. The study applied the Thornthwaite Moisture Index using data on rainfall, temperature, potential evapotranspiration and soil water-holding capacity from 135 Victorian weather stations. This led to the development of soil moisture zones depicting the extent of changes between time periods. The findings hold significant implications for the future of agricultural production and construction suggesting that some practices will cease or shift to different areas. Risk from bushfires may also be increased. The findings point to the importance of soil moisture as one of many important factors contributing to the resilience of complex socio-physical systems.